Associating school doctor interventions with the benefit of the health check: an observational study - Nikander Kirsi; Kosola Silja; Vahlberg Tero; Kaila Minna; Hermanson Elina (BMJ PUBLISHING GROUP, 2022)
Background The benefits of school doctor interventions conducted at routine general health checks remain insufficiently studied. This study explored the associations of school doctor interventions with the doctor-evaluated and parent-evaluated benefits of routine health checks.
Methods Between August 2017 and August 2018, we recruited a random sample of 1341 children from grades 1 and 5 from 21 Finnish elementary schools in 4 municipalities. Doctors routinely examined all children, who were accompanied by parents. The doctor-reported interventions were categorised into six groups: instructions and/or significant discussions, prescriptions, laboratory tests and/or medical imaging, scheduling of follow-up appointments, referrals to other professionals and referrals to specialised care. Doctors evaluated the benefit of the appointment using predetermined criteria, and parents provided their subjective perceptions of benefit. Interventions and reported benefit were compared using multilevel logistic regression.
Results Doctors reported 52% and parents 87% of the appointments with interventions beneficial. All interventions were independently associated with doctor-evaluated benefit (ORs: 1.91-17.26). Receiving any intervention during the appointment was associated with parent-evaluated benefit (OR: 3.25, 95% CI 2.22 to 4.75). In analyses of different interventions, instructions and/or significant discussions (OR: 1.71, 95% CI 1.20 to 2.44), prescriptions (OR: 7.44, 95% CI 2.32 to 23.91) and laboratory tests and/or medical imaging (OR: 3.38, 95% CI 1.34 to 8.55) were associated with parent-evaluated benefit. Scheduled follow-up appointments and referrals to other professionals showed no significant association with parent-evaluated benefit.
Conclusions Doctors and parents valued the appointments with interventions. Parents especially appreciated immediate help and testing from the doctor.